Architecture of Masjid Jamek Sultan Abdul Samad - Jaafar, Badrul Amien; Hakim, Faiz; Roslizam, Hiqmal Nurhakim; Abdul Rahim, Asiah; Zainal Fitri, Nurain Nafisa; Ubaidullah, Syed; Sufian, Rafiqi Aqil (KAED Universal Design Unit (KUDU), 2022)
This chapter will explain the architecture of Masjid Jamek Sultan Abdul Samad. These chapters analyze Masjid Jamek Sultan Abdul Samad from architectural perspective such as Site context, natural and built environment, architectural influence etc,.